Teacher’s Perception on SQ4R in English Reading Comprehension Learning Using Zoom Application - Nurul Lailatul Khusniyah (Universitas Hamzanwadi, 2020)
Learning strategy has an important role in English reading comprehension learning process. To comprehend the text, reading strategy focuses on students’ critical learning. The aims of the study to get teachers’ perception of SQ4R implementation in English reading comprehension learning through zoom application. The method of study used descriptive qualitative. Process of collecting data used observation and questionnaire. The data is taken from the teacher that taught English Reading Comprehension subject in semester two at English Department UIN Mataram. The data analysis used data reduction, data display, and concluding drawing. The result of finding shows that 80% showed a positive attitude towards the implementation of the SQ4R strategy in the English reading comprehension class. This can be seen also from the increase in students' reading comprehension skills. The study results have implications for the suitability of the SQ4R strategy in the reading class through online learning such as zoom